Базові принципи стратегічного управління процесом капіталізації промислового підприємства - Могилова, А.Ю. (Культура народов Причерноморья, 2013)
У статті обґрунтовано важливість вирішення проблеми підвищення капіталізації промислового підприємства. Організація стратегічного управління процесом капіталізації промислового підприємства має будуватися на основі конкретних принципів, стосовно чого було зроблено висновок про неоднозначність поглядів вчених на дане питання, що обумовило необхідність систематизації та вибору основних принципів, які слід закласти в основу стратегічного управління процесом капіталізації промислового підприємства. Комплекс загальних принципів доповнено переліком специфічних принципів, які враховують особливості галузі та технології коньячного виробництва в Україні. Ключові слова: принципи, стратегія, управління, капіталізація, підприємство, промисловість. В статье обоснована важность решения проблемы повышения капитализации промышленного предприятия. Организация стратегического управления процессом капитализации промышленного предприятия должна основываться на конкретних принципах, в отношении чего был сделан взвод о неоднозначности взглядов ученых на данный вопрос, что обусловило необходимость систематизации и отбора основних принципов, которые следует заложить в основу які слід закласти в основу стратегического управления процессом капитализации промышленного предприятия. Комплекс общин принципов дополнен специфическими принципами, которые учитывают особенности отрясли и технологи коньячного производства в Украине. Ключевые слова: принципы, стратегия, управление, капитализация, предприятие, промышленность. With the increased competition between companies for access to limited resources, the process of capitalization of enterprises is of great importance. The organization of the strategic management process of capitalization of industrial enterprises should be based on specific principles. Analysis of the views of many researchers as to what principles must be followed in order to ensure the effectiveness of strategic management, allowed to conclude about the ambiguity of views of scientists on the issue that caused the need for systematization and selection principles that should lay the foundation of the strategic management process capitalization of industrial companies. The complex of general principles was added to the specific principles that lead to effective strategic management and capitalization of industrial enterprises based on industry characteristics and organization of its production process. Thus, the article proposed a list of specific guidelines for a complete cycle of cognac in Ukraine. The author believes that the enforcement of these principles facilitates the solution of complex problems whose solution is within the strategy of increasing the value of the company. Keywords: principles, strategy, management, capitalization, enterprise, industry.